CLASSIFICATION OF ARABIC VERBS (Academia Science Repository, 2023)
The verb as an object of linguistic research is a topic that constantly attracts the attention of researchers. This circumstance is explained by the important role that verbs play in the language system. It is known that the verb in Arabic, in its semantics, conveys the action or state of a person or object and acts as a predicate in a sentence.